Denise Giardina's Storming Heaven: Cultural Marginalization in Appalachia - Fitzgerald, Jason (East Carolina University, 2017)
Using Everett Verner (E.V.) Stonequist's sociological constructs of marginalization and marginal personalities, this study focuses on the extent of marginalization as depicted in Appalachian novelist Denise Giardina's Storming Heaven (1987). In several distinct ways, the novel's protagonists variably adjust to a marginal situation prompted by the early twentieth century arrival of industrial coal companies into West Virginia. Each character responds to the oppression and othering of their Appalachian heritage through attempts to recognize, escape, assimilate, conquer, and/or subvert the marginal situation. Drawing upon Homi Bhabha's postcolonial approach to reading literature as a means of understanding a culture's projection of otherness, this project argues that reading Storming Heaven is reading Giardina's vision of Appalachian culture, unburdened by polarizing stereotypes that frequently accompany outsider narratives of the region and its people.
Keywords: Cultural; Giardina, Denise, 1951-,--Storming Heaven; Marginality, Social--West Virginia; Stonequist, Everett V; Bhabha, Homi K., 1949-; Appalachian Region